Comparative analysis of the SRM as an alternative to the PM motor for automotive applications. Issue 5 (19th August 2014) - Boynov, Konstantin; Paulides, Johannes J.H.; Lomonova, Elena A.; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper presents comparative analysis of several configurations of the switched reluctance motor (SRM) for an in-wheel drive for a heavy-duty automotive series hybrid system. The SRM motor is regarded as one of the primary candidates for possible replacement of the permanent magnet (PM) motor. Design/methodology/approach Three SRMs of 10/8, 12/10 and 12/8 configurations have been analysed, where the last two motors had the stator lamination profile taken from the existing PM motor. The analysis is performed using magnetostatic FEM and transient modelling techniques. Findings The maximum developed electromagnetic torque of the two analysed motors of 12/10 and 12/8 SRM configurations with the stator lamination profile taken from the existing PM motor is limited due to saturation of the stator yoke. Both motor configurations are capable to provide the specified power within the same outer dimensions due to extended speed in the field-weakening region and position independent starting torque. A redesigned stator results in substantial increase in torque developed by the machine and, consequently, ability to provide similar torque-speed performance as the existing PM motor, at cost of increased copper loss at the low-speed regime. Originality/value The paper proposes several structures of SRMs for the in-wheel drive for a heavy-duty automotive series hybrid system converted from the present expensive PM machine, having the same power density. The "bottleneck" of the direct conversion of the PM machine into the SRM is highlighted.